Dampak Kegiatan Penambangan Batu Dan Pasir Terhadap Sosial Ekonomi Masyarakat Di Kanagarian Lubuk Alung Kecamatan Lubuk Alung Kabupaten Padang Pariaman - syahputri, asna wulan (JURNAL BUANA, 2025)
Abstrak This study aims to determine the impact of stone and sand mining activities on the socio-economic community in Kanagarian Lubuk Alung, Lubuk Alung District, Padang Pariaman Regency. This type of research is a type of quantitative research, with data collection techniques using observation and questionnaires, and data analysis techniques using descriptive statistical techniques. The results showed (1) Education, 36% of stone and sand mining workers graduated from junior high school, children of workers aged 7-15 years 71% were in school, and only 37% of family members could read Latin script. (2) Income, Average income of stone and sand mining workers, 69% <Rp 1,500,000, 25% Rp 2,500,000 and 2% >Rp 3,500,000. The average expenditure ranges from IDR 1,000,000 - IDR 5,000,000, to deal with these expenses they carry out survival strategies (active, passive and network). (3). Health 69% of the family's health condition is in good condition in the last 3 months, 49% of couples of childbearing age use family planning, and 34% of the types of family planning used are pills. (4) Family welfare, 27 people (53%) classified as KPS are in Korong Koto Buruak, 19 people (37%) are classified as KS I are in Korong Koto Buruak, and 5 people (10%) are classified as KS II, are in Korong gantiang . Keywords: Mining of stone and sand, socio-economic community